Ketahanan Sosial Keluarga Multiagama dalam Menghadapi Dinamika Pluralitas Masyarakat Desa Linggoasri - Rahmadani, Anisya; Prasetyo, Kuncoro Bayu (Umbara, 2024)
In Linggoasri Village, many families consist of members who practice various religious beliefs. This diversity fosters an atmosphere of tolerance, where individuals respect and embrace each other's differences. This study aims to understand how multi-religious families build social resilience to create harmonious lives and navigate the complexities of a pluralistic society. A qualitative approach was employed, utilizing data collection methods such as field observations, in-depth interviews with multi-religious families, and document analysis. The findings reveal that the social resilience of families in Linggoasri is rooted in key principles: mutual respect, religious freedom, openness to interfaith dialogue, and compassion. These principles are actively practiced in daily interactions, serving as the foundation for fostering harmony. The dynamics of everyday life in such families require a conscious effort to balance the practice of personal beliefs with the need to nurture a sense of togetherness. Pierre Bourdieu's concept of habitus provides a useful framework for understanding these families. Their habitus has evolved within a deeply rooted pluralistic environment, shaping an inclusive society that values mutual respect for religious differences.